2023
DOI: 10.3389/fimmu.2023.1169144
|View full text |Cite
|
Sign up to set email alerts
|

CD26lowPD-1+ CD8 T cells are terminally exhausted and associated with leukemia progression in acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) is a devastating blood cancer with poor prognosis. Novel effective treatment is an urgent unmet need. Immunotherapy targeting T cell exhaustion by blocking inhibitory pathways, such as PD-1, is promising in cancer treatment. However, results from clinical studies applying PD-1 blockade to AML patients are largely disappointing. AML is highly heterogeneous. Identification of additional immune regulatory pathways and defining predictive biomarkers for treatment response are crucial t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Concomitantly to our observations, Zhou et al demonstrated an association between higher frequencies of CD25 low PD-1+ CD8+ T cells and AML progression. That PD-1-expressing population of peripheral blood lymphocytes was significantly lower in subjects with a complete remission to the therapy [ 32 ]. Similarly, PD-1+TIM-3+ effector T cells from bone marrow were also indication of poor therapeutic response, with higher frequency in non-responders [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concomitantly to our observations, Zhou et al demonstrated an association between higher frequencies of CD25 low PD-1+ CD8+ T cells and AML progression. That PD-1-expressing population of peripheral blood lymphocytes was significantly lower in subjects with a complete remission to the therapy [ 32 ]. Similarly, PD-1+TIM-3+ effector T cells from bone marrow were also indication of poor therapeutic response, with higher frequency in non-responders [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A summary of the most recent data on PD-1 expression within immune cells might suggest the possible use of the protein as a target for immunotherapeutic approaches. Considering the indicated exhaustion of the CD8+ T cells, high levels of PD-1-positive cells might be a contradiction to blockage with rhPD-L1 molecules or anti-PD-1 antibodies [ 32 ]. That fact is associated with the resistance of those terminally differentiated immune cells to the specific inhibition, and results in poor clinical outcomes [ 35 ].…”
Section: Discussionmentioning
confidence: 99%